2017
DOI: 10.1038/s41598-017-01621-7
|View full text |Cite
|
Sign up to set email alerts
|

The Brillouin gain of vector modes in a few-mode fiber

Abstract: In this work, we demonstrate the measurement of the Brillouin gain spectra of vector modes in a few-mode fiber for the first time using a simple heterodyne detection technique. A tunable long period fiber grating is used to selectively excite the vector modes supported by the few-mode fiber. Further, we demonstrate the non-destructive measurement of the absolute effective refractive indices (n eff) of vector modes with ~10−4 accuracy based on the acquired Brillouin frequency shifts of the modes. The proposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
(32 reference statements)
0
14
0
2
Order By: Relevance
“…Furthermore, a low uniaxial pressure noticeably reduces the probability of failure in the optical fiber. In this sense, lower uniaxial pressures can be used to inscribe MI-LPFGs by laminated plates, where the results are of great interest in distinct applications [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. On the other hand, the normalized transmission of the leading rejection bands shows similar behavior with respect to the rejection bands in conventional LPFGs, as depicted in Figure 5 d, where one can find good correlation between the experimental results and the theory.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a low uniaxial pressure noticeably reduces the probability of failure in the optical fiber. In this sense, lower uniaxial pressures can be used to inscribe MI-LPFGs by laminated plates, where the results are of great interest in distinct applications [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. On the other hand, the normalized transmission of the leading rejection bands shows similar behavior with respect to the rejection bands in conventional LPFGs, as depicted in Figure 5 d, where one can find good correlation between the experimental results and the theory.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…Additionally, MI-LPFGs are wide tunable with flexible control of depth attenuation and bandwidth of the rejection bands, and they are reversible. These properties make MI-LPFGs attractive for actual uses, such as variable gain shapers, mode converters, wavelength filters, and sensors, among other applications [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As long as the thermo-mechanical response is related to the interaction of the scattered optical mode with the guided (or anti-guided) acoustic wave, both the optical and acoustic properties of the fibers may be functions of the environmental changed parameters. The acoustic-optic interactions in such fibers involve optical and acoustic modes that have the most similar shape with the largest spatial overlap [ 99 ], as demonstrated in [ 100 ] with analysis involving modes possessing orbital angular momentum, while Wu et al [ 101 ] described a hybrid Raman-Brillouin system in a few-mode fiber.…”
Section: Sensing With Specialty Fibers For Simultaneous Temperature and Strain Measurementmentioning
confidence: 99%
“…Weng et al [128] showed that the acousto-optic interactions in such fibers involve optical and acoustic modes that have the most similar shape, and therefore, as would be expected, largest spatial overlap (see Equation (8)). Very nice theoretical analyses of such interactions can be found in [129,130]. Xu et al [62,131] provided an analysis involving modes possessing orbital angular momentum, while Wu et al [132] described a hybrid Raman-Brillouin system in a few-mode fiber.…”
Section: Fiber Configurationsmentioning
confidence: 99%